Assessment of the Research and Production Bridgehead of the Rare Earth Industry of the People’s Republic of China - Kirsanov, Aleksandr; Pervykh, Semjon; Zdonis, Anastasia (New Countryside, 2025)
Since 2010, the growth in demand for and consumption of rare earth elements has more than doubled, due to a fairly wide area of their possible use in various high-tech devices and products. Today, the People’s Republic of China continues to be the world leader in reserves and production output of this type of minerals due to the presence of large deposits, as well as well-structured production chains, which are often combined to create closed cycles for the extraction and processing of rare earth elements. This study provides a comprehensive assessment of China’s rare earth sector by analyzing the structure, specialization, and technological capabilities of major domestic producers. Particular attention is given to their production capacities and innovative technologies. Using publicly available patent data from international sources, the study evaluates the current state of technological development in areas such as mineral extraction, chemical processing, waste minimization, and environmental protection. The analysis confirms that China’s innovation potential in the REE industry continues to grow at a high pace. Moreover, the emergence and expansion of strategic industries based on rare earth materials – such as electric vehicles, wind energy, and advanced electronics—further strengthen the country’s position as a technological leader. The findings provide useful insights for researchers, policymakers, and industry stakeholders interested in sustainable development, strategic resource management, and the future of rare earth innovation in a global context.